Socratic ignorance - Ballard, Edward G. author. aut Link
189 p.
Keywords: This book is intended to offer an interpretation of an important aspect of Plato's philosophy. The matter to be interpreted will be the Platonic myths and doctrines which bear upon self-knowledge and self-ignorance. It is difficult to say in a word just what sort of thing an interpretation is. Rather than attempting to provide a set of rules or meta-rules supposed to define the ideally perfect interpretation, several distinctions will be suggested. I should like to distinguish the philological scholar from the inter preter by saying that the latter uses what the former produces. The function of the scholarly examination of a text is to make an ancient (or foreign) writing available to the contemporary reader. The scholar solves grammatical, lexical, and historical problems and renders his author readable by the person who lacks this scholarly learning and technique. The function of the interpreter is to make use of such available writings in order to render their content more intelligible and useful to a given audience. Thus, he thinks through this content, explains, and re-expresses it in a form which can be easily related to problems, persons, doctrines, or events of another epoch or of another class of readers. At the minimum, the interpretation of a philosophic writing may be thought to prepare its teaching for application to matters which belong in another time or context. Detailed application of a doctrine is, of course, still another thing.